Vitamin D metabolites and risk of first clinical diagnosis of central nervous system demyelination - Tiller, C.; Black, Lucinda; Ponsonby, A.L.; Taylor, B.; van der Mei, I.; Clarke, M.W.; Lucas, R.M. (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
Low 25-hydroxyvitamin D (25(OH)D) concentration is a recognised risk factor for multiple sclerosis (MS). Associations with vitamin D metabolites and vitamin D binding globulin (VDBG) have not been widely studied. We assessed the association between vitamin D metabolites (25(OH)D2, 25(OH)D3, c3-epimer 25(OH)D3, 1,25-dihydroxyvitamin D3 (1,25(OH)2D3), and 24,25-dihydroxyvitamin D3 (24,25(OH)2D3)) measured by liquid chromatography-tandem mass spectrometry assays, VDBG measured using a polyclonal immunoassay, and calculated free and bioavailable 25(OH)D, free 1,25(OH)2D3, and the 24,25(OH)2D3: total 25(OH)D and total 1,25(OH)2D: total 25(OH)D ratios with risk of a first clinical diagnosis of CNS demyelination (FCD) in an Australian case-control study (n = 196 cases, n = 241 controls, matched on age, sex and study region). Higher 25(OH)D (adjusted odds ratio (AOR) = 0.94 (95 % confidence interval (CI) 0.85−1.03) per 10 nmol/L increment) and 24,25(OH)2D3 (AOR = 0.81 (95 %CI 0.65−1.00) per 1 nmol/L increment) concentrations were associated with reduced FCD risk. Our results were compatible with no association for the other vitamin D metabolites, ratios, or VDBG with FCD risk. Thus, using standardised assays, and a comprehensive range of vitamin D metabolites, we confirmed the association of higher 25(OH)D and reduced FCD risk, and describe a similar effect for 24,25(OH)2D3; free or bioavailable 25(OH)D were not associated with FCD risk.